2016
DOI: 10.1186/s40557-016-0139-7
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory heart rate of professional taxi drivers while driving without their typical psychosocial work stressors: a pilot study

Abstract: BackgroundFew studies have examined ambulatory cardiovascular physiological parameters of taxi drivers while driving in relation to their occupational hazards. This study aims to investigate and quantify the impact of worksite physical hazards as a whole on ambulatory heart rate of professional taxi drivers while driving without their typical worksite psychosocial stressors.MethodsAmbulatory heart rate (HRdriving) of 13 non-smoking male taxi drivers (24 to 67 years old) while driving was continuously assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Study sample sizes varied greatly (n = 13-751). With the exception of one study which utilized a stratified random sampling approach (Choi et al, 2016), all employed convenience sampling methods. Fourteen studies were cross-sectional, one study was a 12-week intervention to increase PA among drivers with follow-ups at 4, 8, and 12 weeks (23), and one study was a health fair screening which included follow-ups for insurance, primary care, and additional screenings as appropriate over a six-month period (24).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Study sample sizes varied greatly (n = 13-751). With the exception of one study which utilized a stratified random sampling approach (Choi et al, 2016), all employed convenience sampling methods. Fourteen studies were cross-sectional, one study was a 12-week intervention to increase PA among drivers with follow-ups at 4, 8, and 12 weeks (23), and one study was a health fair screening which included follow-ups for insurance, primary care, and additional screenings as appropriate over a six-month period (24).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies indicated some level of translation or interpretation, with four focus groups in English and one described by the authors as with concurrent Arabic translation (22), focus group facilitators fluent in English and language preferred by the group (5), focus group participants being divided by language (21), multilingual staff surveying participants in their preferred language (27), focus group facilitators fluent in English and Somali (20), questionnaires verbally administered by bicultural research team members (20), and surveys administered orally primarily conducted in English with some partially conducted in Arabic by one of the authors fluent in Arabic (28). Other studies did not report on any translations (4,21,24,(29)(30)(31).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(B. Choi, S. Choi, Jeong, Lee, Shu, Yu, Ko, & Zhu, 2016;Wang & Delp, 2014;Apantaku-Onayemi, Baldyga, Amuwo, Adefuye, Mason, Mitchell, & Blumenthal, 2012;Chen, Chang, Chang, & Christiani, 2005;Hattori & Azami, 2001;Nakano et al, 1998) The relatively high sample size and including different groups of professional light and heavy-vehicle drivers were among the strengths of the present study. Furthermore, a few studies have investigated different domains of stress in professional drivers so far.…”
Section: Discussionmentioning
confidence: 97%